Persepsi terhadap Pengembangan Karir dan Motif Berprestasi pada Distributor Multilevel Marketing - Vitria Rosma Sari; Sus Budiharto (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
The purpose of the present study is to test how the career-development was perceived in relation to the level of achievement motivation for personnel in MLM business. Fifty four (54) distributors as respondents which at least have been joined MLM business for 3 months, were assessed using Perception-on- Career Development's and McClelland Achievement Motivation's Scales. The result shows the more positive the distributors have for their career development in MLM business, the higher their level of achievement motivation will be.